Still willing and able to contribute: donor perspectives on donating blood in later life. (15th April 2021) - Thorpe, Rachel; Masser, Barbara M.; Nguyen, Lilly; Davison, Tanya E.
Abstract : Background and objectives: With greater numbers of Australians living longer with healthier lives, older adults could make a greater contribution to whole‐blood and plasma donor panels. Understanding the experiences and attitudes of middle‐aged to older Australians towards blood donation may provide opportunities to develop strategies to engage, recruit and retain older donors. Methods: Semi‐structured interviews were conducted with 34 donors aged 50 and over with diversity of donation experiences and age at which they first donated. The interviews focussed on becoming and remaining a donor, donating in later life and intentions to continue donating. Results: For some older people, being a blood donor is an important social role associated with a sense of themselves as healthy, knowledgeable and able to make a valuable contribution to the community. The majority of participants believed that age should not be a barrier to continued donation and that eligibility should be based on health and not age. Conclusion: Older donors intend to continue to donate for as long as they are eligible or until they perceive themselves ineligible. Recommendations are provided for strategies to engage with older donors.